Implementasi Perencanaan Strategis SI/TI Pada PT. Prima Teknologi - Rahmad Firdaus; Januar Al Amien (Universitas Bina Darma, 2021)
The use of IS / IT in a company is one of the keys to success in achieving the company's vision, mission and goals. PT. XYZ is a company that has not fully implemented the use of IS / IT to help its business operations, namely in terms of business project management. As time goes by, the impact of the use of IS / IT has not been implemented yet, it is evidenced by the number of project works that experience delays within a certain period of time. In this study, data were obtained from observations, interviews and analysis of company documents. This research refers to the Ward and Peppard method. The results of this study are in the form of a blueprint or description of business strategy, IS / IT management strategy and IT application to achieve corporate strategic goals.